Finding Minimum Distance on Birkhoff-James Orthogonality in Banach Space - Susilo Hariyanto; Titi Udjiani; Yuri C Sagala; Muhammad Rafid Fadil (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
In this paper we define orthogonality concept on Banach space. That is called Birkhoff-Jamesorthogonality. Some new problem about the correlation of orthogonality between Hilbert space and Birkhoff-James were discussed. Correlation investigated by using particular norm. In other side, correlation of minimum distance in Banach space and Birkhoff-James orthogonality also discussed, by generalizing minimum distance in Hilbert space